Songs of ourselves writings by Filipino women in English - Manlapaz, Edna Zapanta (Anvil Publishing, Inc., 1994)
From time to time during the near hundred years of Philippine Literature in English, ... consciousness-of-self-as-Filipino-woman has expressed itself through the voices of writers. But their speech has not always been listened to with the attentiveness conventionally claimed by male discourse. The silent assumption appears to be that women's stories, because often confined within the space of closed rooms and fenced yards, have nothing significant to say about the world outside. Private space cannot accommodate public issues; fairy tales and lullabies and cuentos cannot articulate political statements; small talk cannot en-compass big questions. this anthology does more than affirm these experiences of women as valid and valuable in themselves, its privileges them.